2017
DOI: 10.32502/ecj.v1i2.768
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Comprehension by Using Skimming and Scanning Techniques to the Tenth Grade Students of Sman 1 Gelumbang

Abstract: The objective of this research was to find out whether or not it was effective to teach skimming and scanning techniques in reading a narrative text by the tenth grade students of SMAN 1 Gelumbang. The method used experimental. The population of this study was all tenth grade students of SMAN 1 Gelumbang. The sample of this study was 60 students. It indicated that the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. It could be concluded that it was effective to teach reading com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The CLT method also enabled learners to determine specific information from the text. Here, students determined specific information using the scanning technique, and it is in line with the theory proposed by Marliasari (2017) and Aritonang et al (2018) that scanning enables learners to determine specific information from the text.…”
Section: Discussionmentioning
confidence: 56%
“…The CLT method also enabled learners to determine specific information from the text. Here, students determined specific information using the scanning technique, and it is in line with the theory proposed by Marliasari (2017) and Aritonang et al (2018) that scanning enables learners to determine specific information from the text.…”
Section: Discussionmentioning
confidence: 56%
“…It means that skimming and scanning techniques were adequate to be used for teaching fast and efficient reading comprehension. The research study was connected to previous research by (Marliasari, 2017) her research was carried out at the tenth grade students of SMAN 1 Gelumbang, it was effective to teach reading comprehension by using skimming and scanning techniques, From the score that were found, the result of statistical analysis between experiment and control group (t-obtained) was higher than critical value (0.05) for two tailed. Furthermore the result of the students' score in the experimental group and control group (value of t-obtained) was 3.955.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…Finally, research was read and identified to tackle the problem. For the reading skills, skimming and scanning were used to improve reading comprehension (Marliasari, 2017;Zabrucky & Commander, 1993). There were similar prior practices which were incorporated in the plan.…”
Section: Methodsmentioning
confidence: 99%